Integrating Nutrition Promotion and Rural Development in Sri Lanka - World Bank Group (World Bank, Washington, DC, 2018)
'Integrating Nutrition Promotion and Rural Development' (INPARD) is a multisectoral approach to delivering nutrition-related interventions in rural development programmes in Sri Lanka. Although multisectoral approaches to health promotion are widely recommended, barriers to collaboration across sectors were identified in the INPARD study described in this document. These include a lack of clarity among stakeholders regarding their respective roles, communication gaps between those working in different sectors, and resistance by some who consider health outside the purview of the sector they work in. Improved collaboration will also require training for all concerned. The INPARD study was undertaken to investigate how effectively a rural development programme could be employed to deliver improved human nutrition outcomes – an objective not typically included in traditional rural development interventions in the past. The intervention considered was a large rural development project known as the Re-awakening Project (RaP), which carried out operations in 112 villages in the districts of Ampara and Moneragala. The villages were selected in part on prevailing poverty levels, and 20 of them were randomly selected for evaluation by the INPARD study as it was carried out alongside the larger RaP. 20 other villages in Ampara and Monergala were selected as the control group representing non-RaP villages. Finally, ten villages were selected from outside the RaP area altogether, in Kurungala district.